Cerium‐Modified Mesoporous Antimony Doped Tin Oxide as Intercalation‐Free Charge Storage Layers for Electrochromic Devices. (21st November 2022) - Klein, Jonas; Alarslan, Fatih; Steinhart, Martin; Haase, Markus
Abstract: Charge storage layers are an important component of electrochromic devices, which are expected to exhibit high storage capacity and transparency as well as fast electron transfer rates. However, these layers often rely on the (de)intercalation of ions into the crystal lattice of the material and therefore require optimization to be compatible with non‐intercalating electrolytes. In this report, the post‐modification of mesoporous antimony‐doped tin oxide (ATO) nanoparticle layers with a redox‐active cerium compound is described. In particular, the switching of the Ce 3+ /Ce 4+ couple on the conductive nanoparticle scaffold is demonstrated using tetrabutylammonium perchlorate as a non‐intercalating electrolyte. Remarkably, high storage capacities of up to 27 mC cm −2 and transmittance values of ≈90% are achieved. Variation of the antimony doping concentration revealed that nanoparticle layers doped with 15% Sb exhibit the highest capacity, which can be attributed to increased conductivity in the potential range where the Ce 3+ ions are oxidized. Finally, the cerium‐modified ATO films show promising performance as charge storage layers in an electrochromic device with a viologen‐anchored ATO layer as the electrochromic working electrode. Switching times of ≈0.4 s highlight the fast electron transfer capability of the cerium‐decorated ATO layer, even when a non‐intercalating electrolyte is used. Abstract : Decoration of the inner surface of mesoporous, conducting SnO2 :Sb layers with redox‐active cerium ions greatly enhances their properties as charge storage layers in electrochromic devices. In combination with a non‐intercalating electrolyte, the layers exhibit large charge storage capacities coupled with high transparency as well as fast switching times.